HUBUNGAN TINGKAT STRESS AKADEMIK DAN KEJADIAN GASTROESOPHAGEAL REFLUX DISEASE (GERD) PADA MAHASISWA PROFESI DOKTER PROGRAM STUDI KEDOKTERAN, FAKULTAS KEDOKTERAN UNIVERSITAS BATAM - Muhammad Ali Sabisi; Erika Kusumawardani (Universitas Batam, 2026)
Introduction: Gastroesophageal reflux disease (GERD) is an upper gastrointestinal disorder caused by repeated reflux of gastric contents into the esophagus, leading to symptoms or complications. One of the risk factors for GERD is stress, which is commonly experienced by university students. This study aimed to determine the relationship between academic stress levels and the incidence of GERD among medical professional students of the Medical Study Program, Faculty of Medicine, Universitas Batam. Methods: This study employed a quantitative observational analytic design with a cross-sectional approach and utilized the Chi-square test. Total random sampling was applied based on inclusion and exclusion criteria. GERD was assessed using the GERD-Q questionnaire, while academic stress levels were measured using the Medical Student Stressor Questionnaire (MSSQ). Results: The results showed that a small proportion of students, 14.5% (9 students), experienced GERD symptoms. Nearly half of the respondents, 48.4% (30 students), experienced moderate stress, while 30.6% (13 students) experienced mild stress. A smaller proportion, 19.4% (12 students), experienced severe stress, and only 1.6% (1 student) experienced very severe stress. The Chi-square analysis revealed a p-value of 0.680 (p > 0.05) for the relationship between academic stress level and GERD incidence. Conclusion: There was no statistically significant relationship between academic stress level and the incidence of GERD among medical professional students. Keywords: Gastroesophageal reflux disease, GERD, GERD-Q, MSSQ, Academic stress